2021
DOI: 10.21203/rs.3.rs-259345/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in Conflict Border Regions: A Case of South Kordofan, Sudan

Abstract: The novel coronavirus disease (COVID-19) was first reported in Sudan on 13 March 2020. Since then, Sudan has experienced one of the highest COVID-19 spread and fatalities in Africa. As per 12 December 2020, Sudan had a total of 21,591 cases, 1,355 cumulative deaths at a case fatality rate (CFR) of 6.28%. South Kordofan State has 17.4% COVID-19 case fatality rate, the fifth highest rate among the 18 States. The State is home to over 200,000 poor and displaced people from years of destructive civil unrests. To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Another important factor associated with CSA in the study is gender. Similar to previous studies, while girls were the group with the highest risk of sexual abuse in this study, the number of children arriving during the pandemic period was not different according to gender, compared to the pre-pandemic period (Aslan, Timur&Pakiş, 2020, Güney& Bağ, 2021, Sserwanja et al, 2021, Harris et al, 2021, Alenezi et al, 2022, Augusti et al, 2023. The low number of boys in our study may be related to the patriarchal characteristic of our society.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Another important factor associated with CSA in the study is gender. Similar to previous studies, while girls were the group with the highest risk of sexual abuse in this study, the number of children arriving during the pandemic period was not different according to gender, compared to the pre-pandemic period (Aslan, Timur&Pakiş, 2020, Güney& Bağ, 2021, Sserwanja et al, 2021, Harris et al, 2021, Alenezi et al, 2022, Augusti et al, 2023. The low number of boys in our study may be related to the patriarchal characteristic of our society.…”
Section: Discussionsupporting
confidence: 88%
“…As a matter of fact, studies on epidemics in the past report that the risk of CSA increases, especially among girls (United Nations Development Programme, 2015, International Rescue Committee, 2019. The results of some studies conducted in the Covid 19 pandemic reported that CSA has increased and mostly girls are victims (Sserwanja et al, 2021, Harris et al, 2021, Alenezi et al, 2022, Augusti et al, 2023. A systematic review in which 35 articles were analyzed reported the prevalence of sexual abuse between 1.4% and 19.5% during the pandemic (Huang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%